PENERAPAN MODEL PJBL BERBASIS MEDIA WORDWALL DALAM PEMBENTUKAN KARATER KERJASAMA PADA SISWA SEKOLAH DASAR - Fitriana, Erwinda; Wibawa, Sutrisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study examines the effectiveness of the Project-Based Learning (PjBL) model based on Wordwall media in shaping cooperative character among fifth-grade elementary school students with the topic "Norms in Life". The research was conducted in two cycles of action research. The first cycle involved planning, action, observation, and reflection. Learning activities included role-playing about life norms, supported by Wordwall. The results of the first cycle showed a sufficient level of cooperation, but there was an imbalance in role distribution and communication. The second cycle was carried out with improvements based on the reflection of the first cycle. Observations indicated a significant improvement in student cooperation, particularly in negotiation, group dynamics, and responsibility. The findings suggest that PjBL based on Wordwall successfully enhances students' cooperative character. They become more engaged in learning, improving communication skills, role distribution, and collaborative problem-solving. This indicates that the model can be an effective learning approach in developing cooperation skills among elementary school students.